Functional Models in De Branges Spaces of One Class Commutative Operators - Syrovatskyi, V.N. (Журнал математической физики, анализа, геометрии, 2014)
For a commutative system of the linear bounded operators T₁, T₂, which operate in the Hilbert space H and none of the operators T₁, T₂ is a compression, the functional model is constructed. The model is built for a circle in de Branges space. Для коммутативной системы линейных ограниченных операторов T₁, T₂, которые действуют в гильбертовом пространстве H и ни один из операторов T₁, T₂ не является сжатием, построена функциональная модель. Эта модель строится в пространстве де Бранжа для круга.